Celibacy: Sexuality and Masculinity in Priestly Representations in La Esfinge del Sendero by Jenaro Cardona - Gamboa Gamboa , Wilmer (2024)
In the first decades of the 20th century, a trend that glimpsed in Costa Rican literature moved away from the nationalist discourse imposed by dominant sectors. An example is La esfinge del sendero [The Sphinx of the Path] by Jenaro Cardona, a novel that challenges established norms by addressing the problem of celibacy among priestly figures in rural Costa Rica. Published in 1916, the work contrasts the idealized image of the priesthood with its more degraded version, revealing the tensions between these representations and reflecting the restrictions imposed by the norms of the Catholic Church.